2008
DOI: 10.2147/vhrm.s4196
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of deep venous thrombosis during pregnancy and puerperium in Sudanese women

Abstract: Background: Deep venous thrombosis (DVT) and venous thromboembolism (VTE) is a major health problem with high mortality worldwide. Patients at risk must be identifi ed and given appropriate prophylaxis in order to decrease the mortality. Objective: To investigate the prevalence of DVT in pregnancy and the puerperium and to identify risk factors for DVT. Setting: Khartoum and Khartoum North Teaching hospitals, Sudan. Design: Case-control study. Results: During the study period (April 2007-March 2008, 65 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In our study, median parity of the women was 2 and majority 261(67.8%) were having parity ≤2. In contrast, Gader AA et al observed in their study that primigravida females were at higher risk of developing DVT (p=0.01) 9 .…”
Section: Methodsmentioning
confidence: 72%
“…In our study, median parity of the women was 2 and majority 261(67.8%) were having parity ≤2. In contrast, Gader AA et al observed in their study that primigravida females were at higher risk of developing DVT (p=0.01) 9 .…”
Section: Methodsmentioning
confidence: 72%
“…21 Traditionally, African ethnicity has been associated with a higher prevalence of VTE of 4.48 per 1000 hospital deliveries. 22 In contrast, the prevalence of VTE ranges from 1.7 to 2 per 1000 deliveries in pregnant women of white and Asian ethnicity. 3 Nonetheless, only a few studies have examined the associations in African populations.…”
Section: Discussionmentioning
confidence: 99%
“…Normal venous velocities typically return between weeks 6 and 8 postpartum [31]. 82% of pregnant and postpartum women with DVT have it in their left lower extremity [32]. Possible anatomical causes could be the presence of the right common iliac artery exerting pressure on the left common iliac vein has been observed, which is made worse by the expanding uterus [33].…”
Section: Coagulation Systemmentioning
confidence: 99%